The effect of water and electron collisions in the rotational excitation of HF in comets. Issue 4 (29th August 2022) - Loreau, J; Faure, A; Lique, F
ABSTRACT: We present the first set of rate coefficients for the rotational excitation of the 7 lowest levels of hydrogen fluoride (HF) induced by collision with water molecules, the dominant collider in cometary comas, in the 5–150 K temperature range. The calculations are performed with a quantum statistical approach from an accurate rigid rotor ab initio interaction potential. Rate coefficients for excitation of HF by electron-impact are also computed, within the Born approximation, in the 10–10 000 K temperature range. These rate coefficients are then used in a simple non-local thermodynamic equilibrium (non-LTE) model of a cometary coma that also includes solar radiative pumping and radiative decay. We investigate the range of H2 O densities that lead to non-LTE populations of the rotational levels of HF. We show that to describe the excitation of HF in comets, considering collisions with both water molecules and electrons is needed as a result of the large dipole of HF.